The Urgency of Regional Regulations on the Recognition and Protection of Indigenous Law Communities in Forest Designation Law in Central Kalimantan Province - ., Heriamariaty; Theresia, Louise; Asnawi, Norani (Journal of Ecohumanism, 2024)
Customary forests are forests located within the territories of Indigenous Law Communities. For these communities, customary forests represent their role in safeguarding the sustainability of their forests, which not only protects biodiversity but also preserves invaluable cultural values and ancestral traditions. The designation of customary forests requires a regional regulation to recognize the existence of the Indigenous Law Community, especially if located within state-designated forest areas. Moreover, if the customary forest lies within state forest zones, a regional regulation or a Governor’s and/or Regent/Mayor’s decree is necessary. The conditional recognition of Indigenous Communities suggests that the government has yet to make a strong commitment to formally respect and acknowledge their rights. To date, regulations governing indigenous communities and their traditional rights remain ambiguous and lack definitive protection. The requirements in Article 18B, paragraph (2), along with several statutory conditions related to Natural Resources, show that the state and government recognize and respect customary land rights in a declarative sense but fall short of enacting legal measures to protect and fulfill these rights. The national legal mechanisms remain largely unaddressed, particularly for safeguarding these rights in the event of violations, despite these rights being considered fundamental human rights. For Indigenous Communities, the process of obtaining customary forest designation is often lengthy. First, a regional regulation must establish the Indigenous Community. Next, the area proposed as customary forest is mapped according to the community’s customary regulations. Finally, the ministry processes this request and returns the designation to the local Indigenous Community.